Genomes of Escherichia coli bacteraemia isolates originating from urinary tract foci contain more virulence-associated genes than those from non-urinary foci and neutropaenic hosts. Issue 6 (December 2018) - Dale, Adam P.; Pandey, Anish K.; Hesp, Richard J.; Belogiannis, Konstantinos; Laver, Jay R.; Shone, Clifford C.; Read, Robert C.
Abstract: Objectives: Escherichia coli is the leading cause of bacteraemia. In an era of emerging multi-drug-resistant strains, development of effective preventative strategies will be informed by knowledge of strain diversity associated with specific infective syndromes/patient groups. We hypothesised that the number of virulence factor (VF) genes amongst bacteraemia isolates from neutropaenic patients would be lower than isolates from immunocompetent patients. Methods: Immunocompetent and neutropaenic adults with E. coli bacteraemia were recruited prospectively and the source of bacteraemia determined. VF gene profiles were established in silico following whole genome sequencing. Results: Isolates from individual patients were monoclonal. Strains from immunocompetent patients with urinary tract infective foci (UTIF) harboured more VF genes (median number of VF genes 16, range 8–24) than isolates from both immunocompetent patients with non-UTIF (10, 2–22, p = 0.0058) and neutropaenic patients with unknown focus of infection (NPUFI) (8, 3–13, p < 0.0001). Number of VF genes (OR 1.21, 95% CIs 1.01–1.46, p = 0.039) and urinary catheter/recurrent urinary tract infection (OR 12.82, 95% CIs 1.24–132.65, p = 0.032) were independent predictors of bacteraemia secondary to UTIF vs. non-UTIF in immunocompetent patients. papA, papC, papE/F, papG, agn43, tia, iut, fyuA, kpsM and sat were significantly more prevalent amongst UTIF- vs non-UTIF-originating isolates amongst immunocompetent patients, while papC, papE/F, papG, agn43, tia, fyuA, hlyA, usp and clb were significantly more prevalent amongst UTIF- vs NPUFI-associated isolates. Conclusions: Bacteraemia-associated E. coli strains originating from UTIF have distinct VF gene profiles from strains associated with non-UTIF- and NPUFI. This diversity must be addressed in the design of future vaccines to ensure adequate coverage of strains responsible for site-specific disease.